Physicochemical Characterization and Evaluation of Groundwater Quality in Derna, Libya, Following Hurricane Daniel - Waleed Naser Abumaelumah; Marai A. Mohamed Elkhajkhaj (African Journal of Advanced Pure and Applied Sciences, 2025)
This study aims to determine the safety of groundwater in Derna for human and agricultural use following the extensive flooding and water contamination caused by Hurricane Daniel. Seven representative samples were obtained from wells situated in the most adversely impacted areas. Then, they were tested in a more advanced lab to see if they had Escherichia coli and Total Coliform bacteria. They also checked the pH, electrical conductivity (EC), total dissolved solids (TDS), ammonia (NH₃), nitrate (NO₃⁻), chloride, total hardness, and total hardness. The results showed that most of the samples had levels that were higher than what the World Health Organization (WHO) and Libyan standards say is safe for drinking water. The water had a lot of nitrates, ammonia, and dissolved salts in it, as well as E. coli and Total Coliform. It wasn't safe to drink. A lot of turbidity and chloride were also signs that the water wasn't safe. This was mostly because of flooding that broke pipes and let sewage leak out. The study says we should start using better ways to clean water right away, make systems for checking water quality stronger, and set up programs in communities to teach people about the health risks of dirty water and how important it is to use safe water practices. It also talks about how important it is to make long-term plans for managing water resources so that places that are likely to have disasters have more groundwater and climate change has less of an effect.